2010
DOI: 10.1007/s10493-010-9366-8
|View full text |Cite
|
Sign up to set email alerts
|

Community structure, trophic position and reproductive mode of soil and bark-living oribatid mites in an alpine grassland ecosystem

Abstract: The community structure, stable isotope ratios (15N/14N, 13C/12C) and reproductive mode of oribatid mites (Acari, Oribatida) were investigated in four habitats (upper tree bark, lower tree bark, dry grassland soil, forest soil) at two sites in the Central Alps (Tyrol, Austria). We hypothesized that community structure and trophic position of oribatid mites of dry grassland soils and bark of trees are similar since these habitats have similar abiotic characteristics (open, dry) compared with forest soil. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 48 publications
3
37
3
Order By: Relevance
“…On the other hand, species from the family Eremaeidae were present only in EXT stand. The occurrence of Eremaeus hepaticus, Eueremaeus oblongus and Eueremaeus silvestris is often associated with surface residues (tree bark, branches, decaying wood) left after forest harvesting (Maraun et al 2009;Fischer et al 2010). Maraun & Scheu (2000) observed that Oppiidae are generally abundant in forest soils whereas in strongly disturbed habitats their density is lower, which is in agreement with the distribution of this family in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, species from the family Eremaeidae were present only in EXT stand. The occurrence of Eremaeus hepaticus, Eueremaeus oblongus and Eueremaeus silvestris is often associated with surface residues (tree bark, branches, decaying wood) left after forest harvesting (Maraun et al 2009;Fischer et al 2010). Maraun & Scheu (2000) observed that Oppiidae are generally abundant in forest soils whereas in strongly disturbed habitats their density is lower, which is in agreement with the distribution of this family in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In terrestrial ecosystems, cyanolichens represent a potential source of hepatotoxins for grazers, which might also introduce toxins into food chains. Many molluscs and arthropods, but also mammals such as voles, squirrels, snub-nosed monkeys, and ruminants, are known to feed on lichens (30)(31)(32)(33)(34). Mollusc grazing has been suggested to be the limiting ecological factor for some cyanolichens in boreal rain forests in Norway (31).…”
Section: Discussionmentioning
confidence: 99%
“…Oribatid mite communities on bark overlap only little with those in soil, thereby the bark of trees represents a distinct habitat (Wunderle, 1992;Proctor et al, 2002;Erdmann et al, 2006;Fischer et al, 2010a). However, it is little studied if oribatid mite communities from dead wood on the forest floor resemble those of the soil or those of the bark of trees or if dead wood is colonized by a specific oribatid mite community (but see SkubaƂa and Ma slak, 2009;Huhta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that oribatid mites in soil mostly feed on litter and fungi, whereas oribatid mites on the bark of trees often feed on lichens or mosses (Schuster, 1956;Luxton, 1972;Siepel and de Ruiter-Dijkman, 1993;Erdmann et al, 2007;Fischer et al, 2010a;Maraun et al, 2011). However, the trophic ecology of oribatid mite from dead wood has never been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation